2004
DOI: 10.1016/s0002-9440(10)63164-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Chaperone Protein, Skp, Induces Leukocyte Chemotaxis via C5a Receptor

Abstract: C5a receptor has been identified as a leukocyte chemotactic receptor to two intrinsic chemical mediators, C5a and the S19 ribosomal protein dimer, so far. We found an Escherichia coli protein that also induced the chemotactic responses of monocytes and polymorphonuclear leukocytes via the C5a receptor. We identified the E. coli-derived chemoattractant to be Skp by the molecular size and the N-terminal amino acid sequence. Skp is a periplasmic chaperone protein widely present in gram-negative bacterial species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The OmpH protein of Yersinia shares 66 and 64% amino acid homology with the OmpH proteins of E. coli and Salmonella typhimurium, respectively, and OmpH was predicted to interact with DNA or LPS (41,65). Interestingly, Shrestha et al (66) demonstrated that Skp functions as a chemotactic ligand of the leukocyte C5a receptor, which promotes expression of several other cytokines including IL-1 and IL-6 in monocytes and macrophages and induces mucosal defenses in response to infection (66,67). More importantly, the a1 helix of Skp, whose sequence is homologous to that of the Co1 ligand, plays a pivotal role in C5a receptor activation via phosphorylation of CCR5, suggesting that Co1 may control the activity of other chemoattractants (41,67).…”
Section: Discussionmentioning
confidence: 99%
“…The OmpH protein of Yersinia shares 66 and 64% amino acid homology with the OmpH proteins of E. coli and Salmonella typhimurium, respectively, and OmpH was predicted to interact with DNA or LPS (41,65). Interestingly, Shrestha et al (66) demonstrated that Skp functions as a chemotactic ligand of the leukocyte C5a receptor, which promotes expression of several other cytokines including IL-1 and IL-6 in monocytes and macrophages and induces mucosal defenses in response to infection (66,67). More importantly, the a1 helix of Skp, whose sequence is homologous to that of the Co1 ligand, plays a pivotal role in C5a receptor activation via phosphorylation of CCR5, suggesting that Co1 may control the activity of other chemoattractants (41,67).…”
Section: Discussionmentioning
confidence: 99%
“…Skp, also known as OmpH (outer membrane protein H), is a major structural porin of enteric bacteria such as Escherichia, Klebsiella, Salmonella, and Yersinia (Koski et al, 1989). Skp acts as a cavity chaperone to prevent aggregation (Walton et al, 2009) after forming trimers (Walton and Sousa, 2004) and is also a chemoattractant for both monocytes and polymorphonuclear neutrophils (PMN) (Shrestha et al, 2004). However Skp is not a secretagogue for these cells, unlike C5a, suggesting that it is only a partial agonist.…”
Section: Structure Of Complement Peptidesmentioning
confidence: 99%
“…A comparison of the relative sizes of OmpA and Skp suggests that OmpA is bound in a compacted state, as the unfolded state would be too large to be accommodated by Skp and would therefore be able to interact with other polypeptides (Korndörfer et al, 2004). E. coli Skp has also been identified as a chemoattractant of monocytes and polymorphonuclear leukocytes via the C5a receptor, one of the most important leukocyte receptors involved in the inflammatory reaction (Shrestha et al, 2004). As Skp is widely distributed in Gram-negative bacteria, those authors suggest that recognition of Skp by leukocytes could be of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…benefit to the host innate defence against Gram-negative bacteria (Shrestha et al, 2004). In laboratory strains of E. coli, Skp is not essential for cell viability (Rizzitello et al, 2001), but loss of Skp does lead to a moderate reduction in proteins in the outer membrane (Chen & Henning, 1996).…”
Section: Discussionmentioning
confidence: 99%